H4picoopaRobust Chelate for 225Ac/111In Theranostics - Wharton, Luke; Jaraquemada-Peláez, María de Guadalupe; Zhang, Chengcheng; Zeisler, Jutta; Rodríguez-Rodríguez, Cristina; Osooly, Maryam; Radchenko, Valery; Yang, Hua; Lin, Kuo-Shyan; Bénard, François; Schaffer, Paul; Orvig, Chris (Bioconjugate chemistry, 2022)
The nuclear decay characteristics of 225Ac (E α = 5–8 MeV, linear energy transfer (LET) = ∼100 keV/μm, t 1/2 = 9.92 days) are well recognized as advantageous for the treatment of primary and metastatic tumors; however, suitable chelation systems are required, which can accommodate this radiometal. Since 225Ac does not possess any suitable low-energy, high abundance γ-ray emissions for nuclear imaging, there is a clear need for the development of other companion radionuclides with similar coordination characteristics and comparable half-lives, which can be applied in diagnostics. H4picoopa was designed and executed as a high-denticity ligand for chelation of [225Ac]Ac3+, and the complexation characteristics have been explored through nuclear magnetic resonance (NMR) spectroscopy, solution thermodynamic stability studies, and radiolabeling. The ligand shows highly favorable complexation with La3+ (pM = 17.6), Lu3+ (pM = 21.3), and In3+ (pM = 31.2) and demonstrates effective radiolabeling of both [225Ac]Ac3+ and [111In]In3+ ions achieving quantitative radiochemical conversions (RCCs) under mild conditions (RT, 10 min), accompanied by high serum stability (>97% radiochemical purity (RCP) over 6 days). A bifunctional analogue of H4picoopa was synthesized and conjugated to the Pip-Nle-CycMSHhex peptide for targeting of MC1R positive melanoma tumors. In vivo single-photon emission computed tomography (SPECT) and biodistribution studies of the 111In-radiolabeled bioconjugate in mice bearing B16-F10 tumors showed good radiotracer stability, although improved tumor targeting could not be achieved for imaging purposes. This work highlights H4picoopa as a very promising platform for application of [225Ac]Ac3+ and [111In]In3+ as a theranostic pair and allows great versatility for the incorporation of other directing vectors. The logical synthetic approach reported here for bifunctional H4picoopa, involving an azide-functionalized covalent linker and CuI-catalyzed alkyne-azide cycloaddition, allows for ease of optimization of bioconjugate pharmacokinetics and will be valuable for further radiopharmaceutical applications moving forward.